Theoretical research of cleaner pressure on sugar beet root crop - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Nikolaenko, S.; Boris, M.; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2017)
Technology incompatibility in the sugar beet harvesting process is established. Beet tops removing by follower cutoff with the subsequent root crop heads cleaning is possible at speed no more than 1.5 m·s-1 whereas beet pullers operate at speeds of 1.2... 1.5 times are higher. At a cutting without copier of sugar beet tops a working speed makes more than 1.5 m·s-1, however losses of sugar-bearing plant material exceed agrotechnical requirements twice because of unreasonable height of a cut relative to soil surface. The differential equation of bow-shaped copier movement on a root crop head of sugar beet which is the main equation of functioning root crops heads cleaner is worked out. Components of the differential equation are defined and dependence of normal reaction on design parameters of root crop head cleaner is received. Conditions not of knocking-out of root crops are received and rational values of design parameters and operating modes of root crop head cleaner are proved.
Keywords: root crop; beet tops; root crop head; cleaner; working member; sensing member; normal reaction; defoliator